Upaya Peningkatan Kemampuan Menyusun Bahan Ajar Online Bagi Guru Bahasa Arab di Kabupaten Ponorogo - Ali Ba’ul Chusna; Ahmad Mujib; Kholidah Antun Firdausi (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
The need for teaching materials becomes something very important in learning activities. Especially during the current covid-19 pandemic where learning activities that are usually carried out face-to-face are directly replaced with distance learning by utilizing technological sophistication as a medium. In this case, teachers are required to be able to prepare teaching materials properly so that learning activities will continue to take place well, effectively, efficiently, and fun. This article aims to describe efforts to increase teacher competence in compiling online teaching materials for Arabic language teachers in the Ponorogo Regency area and the results achieved after participating in the preparation of online teaching materials. The service method used is participatory action research (PAR) which consists of four stages, namely mapping or problem mapping; action planning; implementation of actions; and evaluation. Efforts to improve the ability to compose online teaching materials were carried out in the form of training which was attended by 16 teachers from both Tsanawiyah and Aliyah madrasas in the Ponorogo Regency area. This activity was carried out in two stages with the presenters being the teaching team consisting of lecturers in the Arabic Language Education Department of IAIN Ponorogo. The material presented is the preparation of teaching materials based on power point and video. The results of the service show that participants are able to compile teaching materials using power point programs and videos to then be uploaded as online learning media.